The Ship That Held Up Wall Street : The Ronson Ship Wreck - Riess, Warren (Book collections on Project MUSE., 2014)
In January 1982, archaeologists conducting a pre-construction excavation at 175 Water Street in Lower Manhattan found the remains of an eighteenth-century ship. Uncertain of what they had found or what its value might be, they called in two nautical archaeologists-Warren Riess and Sheli Smith-to direct the excavation and analysis of the ship's remains. As it turned out, the mystery ship's age and type meant that its careful study would help answer some important questions about the commerce and transportation of an earlier era of American history. The Ship that Held Up Wall Street tells the whole story of the discovery, excavation, and study of what came to be called the "Ronson ship site," named for the site's developer, Howard Ronson. Entombed for more than two hundred years, the Princess Carolina proved to be the first major discovery of a colonial merchant ship. Years of arduous analytical work have led to critical breakthroughs revealing how the ship was designed and constructed, its probable identity as a vessel built in Charleston, South Carolina, its history as a merchant ship, and why and how it came to be buried in Manhattan